Vietnam : Adapting to an Aging Society - World Bank (World Bank, Hanoi, 2021)
Vietnam is a young country on the cusp of a dramatic aging of the population that is taking place at a faster pace and at an earlier level of development than most other countries in the world. Though Vietnam’s favorable demographic window of opportunity is still open, this report argues it should take key actions with immediate effect to prepare for a rapidly aging society. Vietnam has achieved vibrant economic growth and poverty reduction over the past few decades, thanks in large part to favorable demographic trends along with strong productivity growth. Growth and poverty reduction have been broad based to-date, and between 2010 to 2016, older generations benefited the most relative to the other age groups from poverty reduction. Increased productivity and labor force participation can help to mitigate the adverse impacts of a shrinking working-age population. Evidence suggest Vietnam’s youth are already investing more in human capital than their elders. Encouraging people to continue working even when they grow older can also help compensate for the shrinking labor force.